Exploring Value Co-Creation in Sharing Platforms by Applying DART Framework - Svarcaite, Asta; Gadeikiene, Agne (Organizations and Markets in Emerging Economies, 2023)
The spread and development of sharing platforms can be seen in many countries around the world, especially in emerging economies. However, sharing platforms face challenges in retaining users and attracting new ones. The value co-creation can be used as a tool to ensure competitiveness, develop innovation, and strengthen relationships with consumers. Thus, this study aims to explore value co-creation in sharing platforms from the perspective of platform developers by applying the DART framework. Case study analysis was applied to the empirical study. Its results indicate that the dialogue dimension unfolds through interaction; the access develops through information and tools; the risk-benefit reveals the disadvantages of sources and the possible risks of using the sharing platform; the transparency is exposed through transparency about user reliability. A new sub-dimension emerges in the dialogue dimension – ‘networking’, where platform actors can participate in value co-creation as user groups and foster innovation. Since information overload can lead to undesirable user behavior, we propose to assess the ‘navigation’ sub-dimension by analyzing the access dimension. The results of the study contribute to value co-creation scientific literature by extending and adapting the DART framework for sharing-based business models and provide useful practical insights for sharing platform developers.